2018
DOI: 10.17219/acem/70226
|View full text |Cite
|
Sign up to set email alerts
|

Obesity without comorbidity may also lead to non-thyroidal illness syndrome

Abstract: Inflammation, which is strongly associated with adipose tissue, may lead to NTIS in obese patients without any comorbid disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Moreover, FT3 level is difficult to interpret because many acute or chronic extra-thyroidal conditions (involving nutritional status and systemic inflammation) can reduce the conversion of T4 to T3, a mechanism known as 'nonthyroidal illness', 'euthyroid sick syndrome' or 'low-T3 syndrome' (51). There are very few data on the incidence of non-thyroidal illness in the obese population but one publication suggested that inflammation may increase non-thyroidal illness in obesity (52). In contrast, FT3 has been described to be higher in obesity than in lean people, this being mainly related to the nutritional status (53).…”
Section: Reasoningmentioning
confidence: 99%
“…Moreover, FT3 level is difficult to interpret because many acute or chronic extra-thyroidal conditions (involving nutritional status and systemic inflammation) can reduce the conversion of T4 to T3, a mechanism known as 'nonthyroidal illness', 'euthyroid sick syndrome' or 'low-T3 syndrome' (51). There are very few data on the incidence of non-thyroidal illness in the obese population but one publication suggested that inflammation may increase non-thyroidal illness in obesity (52). In contrast, FT3 has been described to be higher in obesity than in lean people, this being mainly related to the nutritional status (53).…”
Section: Reasoningmentioning
confidence: 99%
“…To our current knowledge this is the first paper to report uncoupling excessive weight gain from inflammation. However, there is some supporting data in the literature reporting that few individuals with BMI close to or above 30 can have low CRP levels [40,41,42], thus, obesity does not necessarily cause inflammation in each individual. We hypothesize that different response to the adipose tissue expansion and/or missing inflammatory mediators may be responsible for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of obesity are widespread and related to multiple comorbidities, including cardiovascular diseases, type 2 diabetes, dyslipidemia, hypertension, and other chronic disorders 3 . In addition, hypertrophic fat tissue resulting from obesity leads to increasing levels of inflammation with excessive release of pro-inflammatory cytokines, such as interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), and C-reactive protein (CRP) 4 5 .…”
Section: Introductionmentioning
confidence: 99%
“…As evidence of inflammation, high levels of erythrocyte sedimentation rate (ESR) and some complete blood count parameters were found 5 . Leukocytes (LE) or white blood cells form part of the immune system and are closely linked to the inflammatory response, and their levels are associated with metabolic and cardiovascular disorders caused by obesity 6 .…”
Section: Introductionmentioning
confidence: 99%